Bilayer goat’s milk yogurt with tamarind (Tamarindus indica L.) and wild passion fruit (Passiflora cincinnata Mast) jam: Characterization and acceptability (Research, Society and Development, 2020)
The aim of this study was to develop a goat's milk-based yogurt with a layer of tamarind and passion fruit jelly on the bottom of the package (bilayer yogurt) as well as to carry out the physical-chemical, microbiological and sensory characterization. of product. For comparison purposes, goat's milk products were compared with the same cow's milk product. The physicochemical analyzes showed that the samples are within the standards of the legislation, both for yogurts and jams. Regarding microbiological analyzes, there was no microbial growth in any of the samples evaluated. Sensory tests were carried out with 60 tasters that were aged between 14 and 32 years. Sensory attributes related to “appearance”, “color”, “aroma”, “consistency” and “flavor” were evaluated, among them only consistency showed a significant difference due to the chemical characteristics of goat's milk, however, in percentage values goat's milk yogurt was rated with the highest grades. In the global impression and purchase intention, the analysis of the data obtained showed that the values attributed by the tasters are located in the highest scores of the hedonic scale. Thus, for bilayer goat's milk yogurts with tamarind or wild passion fruit jams, the results are favorable and highly acceptable. These results denote the possibility of insertion of these new products in the regional market in view of the acceptance of the product by the tasters as well as the intention to purchase, in addition to the appreciation of the regional fruits present in the jams elaborated.